Laparoscopic repeat liver resection after open liver resection: A comparative study from a single-centre - Taiga Wakabayashi (Journal of Minimal Access Surgery, 2020)
Background: Technological innovations have made it possible to use laparoscopic liver resection in cases with pre-existing adhesions or cicatricial changes. However, laparoscopic repeat liver resection (LRLR) still represents a challenge for surgeons, especially in case of previous open liver surgery. This study evaluated the outcomes of LRLR after open liver resection (OLR) in cases of recurrent liver cancer. Materials and Methods: A total of 62 patients who underwent laparoscopic minor liver resection at our institution between September 2012 and September 2016 were retrospectively divided into an LRLR group (n = 13) and a laparoscopic primary liver resection group (LPLR; n = 49). The two groups were compared in terms of patient demographics, surgical procedures and short-term outcomes. Recurrence-free survival (RFS) and overall survival (OS) were compared for patients with hepatocellular carcinoma (HCC) or colorectal liver metastases (CRLMs). Results: There was a significant intergroup difference in the hepatitis virus background, although the two groups' primary histology and pre-operative liver function were comparable. The two groups had statistically similar values for extent of resection, operative time, estimated blood loss, transfusion requirement, conversion to laparotomy, post-operative complications, surgical margins, time to oral intake and hospital stay. No significant differences were detected when we stratified the cases according to low and intermediate difficulty. Furthermore, there were no intergroup differences in RFS or OS in the two groups for patients with HCC and CRLM. Conclusions: The findings suggest that minor LRLR after OLR is safe and comparable with minor LPLR in the present study.